Information and communications technology acceptance among Malaysian adolescents in urban poverty - Halili, S.H.; Sulaiman, H.; Rafiza, A.R. (2017)
This study was conducted to identify the information communication and technology (ICT) usage among adolescents in urban poverty and their acceptance of using ICT in teaching and learning (T&L) process. The Technology Acceptance Model was used in determining the acceptance of ICT by focusing on factors such as perceived ease of use and perceived usefulness as the two main factors that is much referred for technology acceptance. This case study was conducted using a quantitative and a questionnaire was used to collect data from 50 respondents. SPSS software was used in the form of descriptive statistics. the result showed that majority of the respondents do not spend much time in using ICT at home or even during class session. However, their acceptance in using ICT are positive in T&L process. Based on the findings, suggestions have been proposed to increase the effective use of ICT among adolescents in urban poverty.